Cultural Village Jalawastu as a manifestation of multicultural tourism in Javanese and Sundanese society (Jasun): literature review - Setiyoko, Didik Tri; Banowati, Eva; Priyanto, Agustinus Sugeng; Purnomo, Arif (Universitas Negeri Semarang, 2024)
. This research aims to map the tourism potential in Jalawastu Cultural Village and develop sustainable community-based tourism. Historical information is needed to understand the values of local wisdom and to inventory the potentials and tourist attractions in Jalawastu Cultural Village. The urgency of this research lies in the conservation and development of cultural heritage. By identifying the cultural tourism potentials in Jalawastu Cultural Village, this research will also assist in the efforts to conserve and develop local cultural heritage. This is crucial for preserving unique cultural identities and preventing the loss of traditional knowledge and practices. The development of multicultural community-based tourism is a concept that combines cultural richness, local wisdom, and active community participation in managing tourist destinations. In the context of Javanese and Sundanese (Jasun), Jalawastu Cultural Village represents a particularly interesting potential. Located on the border between the Javanese and Sundanese regions, this village showcases rich cultural diversity and can attract both local and international tourists. The research method to be used is qualitative with an literature riview. The results of this study indicate that Jalawastu Cultural Village has great potential to be developed into a community-based multicultural tourism destination. The role of the local government is crucial in promoting Jalawastu Cultural Village to be more widely recognized internationally.